Photocatalytic of anionic dyes on Congo red with M2+/Al (M2+=Ni, Mg, and Zn) layered double hydroxide intercalated polyoxometalate - Hanifah, Yulizah; Mohadi, Risfidian; Mardianto; Nur Ahmad; Suheryanto; Lesbani, Aldes (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2023)
The modification catalysts of layered double hydroxide (LDH) with polyoxometalate based on Keggin type were prepared and characterized using X-Ray, FTIR, and SEM to confirm the layered double hydroxide structure. Intercalation was successfully synthesized and showed a heterogeneous aggregate resulted from SEM analysis. The degradation parameters of LDH pristine and LDH composite were determined by observing a number of factors such as pH, catalyst weight, and degradation time. The modification material resulted by preparation material LDH and polyoxometalate (POM) successfully resulted in the lower band gap value compared to material pristine LDH allowing LDH polyoxometalate as photocatalysts to show good photocatalytic activities. The NiAl-SiW12O40 material had the highest percentage of degradation removing Congo Red up to 86% degradation when compared to another composite material, yet it was still significantly better than LDH pristine. The result showed that the LDH composite presented excellent photocatalytic activity in reducing Congo Red.